The Role of Organizational Commitment in Mediating the Effect of Self-Efficacy and Work-Life Balance on Employee Performance at the Population and Civil Registration Office of Badung Regency - Ni Putu Putri KRISNAYANTI; Ni Wayan SITIARI; Ida Ayu SURASMI (PT Keberlanjutan Strategis Indonesia, 2025)
The existence of Civil Servants (PNS) in government agencies, as a cog in all government activities must be able to carry out duties and obligations based on a code of ethics that has been determined and regulated in government regulations. This study aims to analyze the effect of Self-efficacy and work-life balance on employee performance with organizational commitment as mediation. Data was collected using a questionnaire to 40 respondents who were employees of the Badung Regency Population and Civil Registry Office. Hypothesis testing is done using inferential analysis using PLS. The results showed that Self-efficacy has a positive and significant effect on employee performance and organizational commitment. Work-life balance has a positive and significant impact on employee performance and organizational commitment. Organizational commitment has a positive and significant effect on employee performance. In addition, organizational commitment can partially mediate the effect of Self-efficacy and work-life balance on employee performance.